PHYSICAL ACTIVITY AS A PREDICTOR OF COLLEGE STUDENT HAPPINESS ACROSS GENDER DIFFERENCES - Maulidiyah, Elok Faiqoh; Jannah, Miftakhul (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
The academic demands often experienced by college students and a sedentary lifestyle that is not balanced with physical activity affect their psychological well-being, such as a decrease in happiness levels. This study aims to determine physical activity as one of the predictors of happiness among college students, moderated by gender. A non-experimental quantitative method was chosen as the research method, with a cross-sectional design. The total of research respondents was 230 college students selected through purposive sampling. The measurement tools used were the International Physical Activity Questionnaire (IPAQ) for physical activity variables and the Oxford Happiness Questionnaire to measure happiness, both of which have been proven to be valid and reliable. Data analysis techniques used Multiple Regression Analysis (MRA) through JASP 0.95.2 software. Physical activity was found to have a positive effect on college student happiness (? = 0.208; p < 0.01), and gender was able to moderate the relationship between physical activity and happiness (? interaction = 0.556; p < 0.01), with a stronger effect on female college students than male college students. The results of this study contribute theoretically to the understanding of physical activity factors that can affect subjective well-being among college students, while also providing practical implications for further promoting healthy lifestyles through physical activity in higher education institutions, with consideration given to gender.